2018
DOI: 10.1128/aac.01886-17
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibility of Emerging Dimorphic Pathogens in the Family Ajellomycetaceae

Abstract: The susceptibilities of 24 molecularly identified dimorphic fungi belonging to the genera, , and within the family were tested against 8 standard antifungal agents using CLSI document M38-A2. Amphotericin B and posaconazole had the lowest geometric mean MICs (<0.05 μg/ml) followed by itraconazole (<0.07 μg/ml), voriconazole (<0.15 μg/ml), and isavuconazole (<0.42 μg/ml) while fluconazole was not active. Micafungin demonstrated good antifungal activity against (geometric mean minimum effective concentration [GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…canadensis isolates found MICs elevated for fluconazole and low for itraconazole and amphotericin B. Dukik et al ( 12 ) recently reported antifungal susceptibility results for 2 Es. canadensis isolates including UAMH 7172 (reported as CBS 139872) and UAMH 10370 (reported as CBS 1398723 The authors similarly found that MICs were elevated for fluconazole and low for newer triazoles and amphotericin B ( 12 ). These findings are consistent with the antifungal susceptibility patterns reported for 50 Es.…”
Section: Discussionmentioning
confidence: 99%
“…canadensis isolates found MICs elevated for fluconazole and low for itraconazole and amphotericin B. Dukik et al ( 12 ) recently reported antifungal susceptibility results for 2 Es. canadensis isolates including UAMH 7172 (reported as CBS 139872) and UAMH 10370 (reported as CBS 1398723 The authors similarly found that MICs were elevated for fluconazole and low for newer triazoles and amphotericin B ( 12 ). These findings are consistent with the antifungal susceptibility patterns reported for 50 Es.…”
Section: Discussionmentioning
confidence: 99%
“…Conidia are not produced in vitro, and thus the risk of occupational inhalational exposure is considered low, although primary inoculation disease, may be possi- ble. In vitro antifungal susceptibility results suggested susceptibility to amphotericin B and extended azoles (Dukik et al 2017a). National level biosafety risk assessments for B. helicus do not yet exist.…”
Section: Biosafety Considerationsmentioning
confidence: 99%
“…Swollen hyphae and conidia becoming giant cells with rather thick walls, some showing broad-based budding. Scale bars: D-M = 10 lm results showed susceptibility to amphotericin B, itraconazole, voriconazole and caspofungin (Borman et al 2009;Dukik et al 2017a). However, the role of antifungal therapy is controversial, because in vivo replication does not occur (Anstead et al 2012).…”
Section: Biosafety Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human blastomycosis is caused by three distinct species within the Blastomyces genus . B. dermatitidis and B. gilchristii cause infections mostly in North America, whereas B. percursus has been found in South Africa and Israel [1] , [2] . The symptoms of blastomycosis range from asymptomatic infection to fulminant respiratory failure with acute respiratory distress syndrome and/or dissemination to skin, bone, and other organs.…”
Section: Introductionmentioning
confidence: 99%